Tyr-Trp administration facilitates brain norepinephrine metabolism and ameliorates a short-term memory deficit in a mouse model of Alzheimer’s disease - Ichinose, Takashi; Murasawa, Hiroyasu; Ishijima, Tomoko; Okada, Shinji; Abe, Keiko; Matsumoto, Saki; Matsui, Toshiro; Furuya, Shigeki (PLOS ONE, 2020)
The physiological actions of orally ingested peptides on the brain remain poorly understood. This study examined the effects of 39 orally administered synthetic Tyr-containing dipeptides on the enhancement of brain norepinephrine metabolism in mice by comparing the concentration of 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG). Although Tyr-Tyr administration increased blood and cerebral cortex (Cx) Tyr concentrations the most, Tyr-Trp increased Cx MHPG concentration the most. The oral administration of Tyr-Trp ameliorated a short-term memory deficit of a mouse model of cognitive dysfunction induced by amyloid beta peptide 25–35. Gene expression profiling of mouse brain using a microarray indicated that Tyr-Trp administration led to a wide variety of changes in mRNA levels, including the upregulation of genes encoding molecules involved in catecholamine metabolism. A comparative metabolome analysis of the Cx of mice given Tyr-Trp or Tyr-Tyr demonstrated that Tyr-Trp administration yielded higher concentrations of Trp and kynurenine pathway metabolites than Tyr-Tyr administration, as well as higher L-dopa levels, which is the initial product of catecholamine metabolism. Catecholamines were not significantly increased in the Cx of the Tyr-Tyr group compared with the Tyr-Trp group, despite a marked increase in Tyr. Presumably, Tyr-Trp administration enhances catecholamine synthesis and metabolism via the upregulation of genes involved in Tyr and Trp metabolism as well as metabolites of Tyr and Trp. These findings strongly suggest that orally ingested Tyr-Trp modulates the brain metabolome involved in catecholamine metabolism and contributes to higher brain function.